MiR-431-5p Knockdown Protects Against Angiotensin II–Induced Hypertension and Vascular Injury. Issue 5 (May 2019) - Huo, Ku-Geng; Richer, Chantal; Berillo, Olga; Mahjoub, Nada; Fraulob-Aquino, Julio C.; Barhoumi, Tlili; Ouerd, Sofiane; Coelho, Suellen C.; Sinnett, Daniel; Paradis, Pierre; Schiffrin, Ernesto L.
Abstract : Vascular injury is an early manifestation in hypertension and a cause of end-organ damage. MicroRNAs play an important role in cardiovascular disease, but their implication in vascular injury in hypertension remains unclear. This study revealed using an unbiased approach, microRNA and mRNA sequencing with molecular interaction analysis, a microRNA-transcription factor coregulatory network involved in vascular injury in mice made hypertensive by 14-day Ang II (angiotensin II) infusion. A candidate gene approach identified upregulated miR-431-5p encoded in the conserved 12qF1 (14q32 in humans) microRNA cluster, whose expression correlated with blood pressure, and which has been shown to be upregulated in human atherosclerosis, as a potential key regulator in Ang II–induced vascular injury. Gain- and loss-of-function in human vascular smooth muscle cells demonstrated that miR-431-5p regulates in part gene expression by targeting ETS homologous factor. In vivo miR-431-5p knockdown delayed Ang II–induced blood pressure elevation and reduced vascular injury in mice, which demonstrated its potential as a target for treatment of hypertension and vascular injury. Abstract : Supplemental Digital Content is available in the text.